Integrated Proteomic and Metabolomic Profiling of Phytophthora cinnamomi Attack on Sweet Chestnut (Castanea sativa) Reveals Distinct Molecular Reprogramming Proximal to the Infection Site and Away from It - Saiz Fernandez, Inigo; Milenković, Ivan; Berka, Miroslav; Černý, Martin; Tomšovský, Michal; Brzobohatý, Břetislav; Kerchev, Pavel (MDPI AG (Multidisciplinary Digital Publishing Institute-MDPI), 2020)
Phytophthora cinnamomi is one of the most invasive tree pathogens that devastates wild and cultivated forests. Due to its wide host range, knowledge of the infection process at the molecular level is lacking for most of its tree hosts. To expand the repertoire of studied Phytophthora-woody plant interactions and identify molecular mechanisms that can facilitate discovery of novel ways to control its spread and damaging effects, we focused on the interaction between P. cinnamomi and sweet chestnut (Castanea sativa), an economically important tree for the wood processing industry. By using a combination of proteomics, metabolomics, and targeted hormonal analysis, we mapped the effects of P. cinnamomi attack on stem tissues immediately bordering the infection site and away from it. P. cinnamomi led to a massive reprogramming of the chestnut proteome and accumulation of the stress-related hormones salicylic acid (SA) and jasmonic acid (JA), indicating that stem inoculation can be used as an easily accessible model system to identify novel molecular players in P. cinnamomi pathogenicity.
Keywords: Metabolomics; Phytophthora cinnamomi; Proteomics; Sweet chestnut